Morphologic and Hemodynamic Risk Factors in Ruptured Aneurysms Imaged before and after Rupture - Chien, A.; Sayre, J. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Due to limited information about aneurysm natural history, choosing the appropriate management strategy for an unruptured aneurysm is challenging. By comparing unruptured and ruptured cases, studies have identified a variety of aneurysm morphologic and hemodynamic properties as risk factors for rupture. In this study, we investigated changes in 4 ruptured aneurysms before and after rupture and tested whether previously published risk factors identified a risk before rupture. MATERIALS AND METHODS: A retrospective review of ruptured aneurysms based on the inclusion criteria of documenting angiographic images before and after rupture was performed. Such cases are extremely rare. To minimize hemodynamic influence due to location, we selected 4 cases at the posterior communicating artery. 3D morphologic and hemodynamic analyses were applied to examine qualitative and quantitative risk factors in aneurysms before and after rupture. RESULTS: When we compared aneurysms before and after rupture, all increased in size. Volume, surface area, and morphology changed in both high and low wall shear stress areas. Aneurysm surface ratio, nonsphericity index, and pulsatility index were the only risk factors to consistently identify risk before and after aneurysm rupture for all aneurysms. CONCLUSIONS: Although changes in shape and flow properties were found before and after aneurysm rupture, in this small study, we found that some risk factors were evident as early as 2 years before rupture. AASAaneurysm surface area to sphere surface area ratioAVSVaneurysm volume to sphere volume ratioNSInonsphericity indexPIpulsatility indexSRsize ratioWSSwall shear stress